Effects of tofacitinib therapy on arginine and methionine metabolites in association with vascular pathophysiology in rheumatoid arthritis: A metabolomic approach - Soós, Boglárka; Hamar, Attila; Pusztai, Anita; Czókolyová, Monika; Végh, Edit; Szamosi, Szilvia; Pethő, Zsófia; Gulyás, Katalin; Kerekes, György; Szántó, Sándor; Szűcs, Gabriella; Christians, Uwe; et al. (Frontiers in Medicine, 2022)
Introduction. Rheumatoid arthritis (RA) is associated with changes in lipid, arginine and NO metabolism with increased cardiovascular (CV) risk. We wished to evaluate the effect of tofacitinib, a JAK inhibitor, on arginine and methionine metabolism in correlation with inflammation, functional and pathological vascular changes during one-year treatment. Methods. Thirty RA patients with active disease were treated with either 5 mg bid or 10 mg bid tofacitinib for 12 months. We determined DAS28, CRP, IgM rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) levels. We assessed brachial artery flow-mediated vasodilation (FMD), carotid intima-media thickness (IMT) and pulse-wave velocity (PWV) by ultrasound at baseline, after 6 and 12 months. We also determined plasma L-arginine, L-citrulline, L-ornithine, inducible nitric oxide synthase (iNOS), asymmetric (ADMA) and symmetric dimethylarginine (SDMA), L-N-monomethyl-arginine (L-NMMA), cysteine, homocysteine, and methionine levels at these time points. Results. Twenty-six patients (13 on each arm) completed the study. CRP, ESR and DAS28 decreased significantly during one-year treatment with tofacitinib. Arginine and ADMA showed a negative univariate correlation with CRP but not with FMD, PWV or IMT. Tofacitinib at 10 mg bid significantly increased L-arginine, L-ornithine, iNOS and methionine levels after 12 months. ADMA and SDMA levels did not change in our study. Methionine showed negative correlation with FMD at baseline and positive correlation with PWV after 12 months. No change was observed in FMD and PWV but a significant increase was measured in IMT at 6 and 12 months. Multivariate analysis indicated variable correlations of L-arginine, L-citrulline, ADMA, L-NMMA, homocysteine and methionine with DAS28, CRP, ESR and RF but not with anti-CCP after one-year treatment. With respect to vascular pathophysiology, only PWV and methionine correlated with each other. Conclusions. One-year tofacitinib treatment suppressed systemic inflammation and improved functional status in RA. FMD, PWV have not been affected by one-year tofacitinib treatment., while IMT increased further despite treatment. Increased arginine and methionine might contribute to the anti-inflammatory effects of tofacitinib. Increased arginine availability with no changing ADMA may protect FMD and PWV from deterioration. The increase of IMT in the anti-inflammatory environment cannot be explained by arginine or methionine metabolism in this study.